A comparative study of Texas–Mexico border vs. non-border students’ achievement on high-stakes state test: A propensity score matching method - Wang, Zhuoying; Tang, Shifang; Luo, Feng (Frontiers in Education, 2023)
Texas-Mexico border region is a unique place where two countries and culture connected. We sought to investigate border school district students’ academic performance as measured by Texas standardized test: the State of Texas Assessments of Academic Readiness (STAAR). To do so, we first used propensity score matching (PSM) techniques to analyze data collected from a public database: Texas Assessment Management System (TAMS). Specifically, we provided a PSM analysis of non-border and border school districts regarding their demographic characteristics (i.e., identified as a rural district, percentage of economically disadvantaged (ED)students, percentage of English learners (ELs), mobility rate, instructional hours, principal experience, teacher experience, teacher-student ratio and teacher turnover rate). Then, multiple regression analyses were conducted to compare Texas border and non-border school students’ reading, math, and science achievements, respectively, based on a matching sample with control for demographic variables. The results of the current study indicate that no significant difference was found between border and non-border school districts, regarding students’ academic performance in reading, math, and science, when districts were matched and demographic characteristics were controlled. We further found that demographic variables, such as percent of ED students, principal experience, and teacher turnover rate, significantly impact students' academic achievement. Such findings have suggested that the achievement gap between border and non-border districts can be closed if extra support can be provided to ED students, and fundings could be allocated in border districts to maintain experienced principals and teachers.